Diagnostic role of contrast-enhanced voiding urosonography (ceVUS) in pediatric duplex kidneys – a comparison with voiding cystourethrography (VCUG) - Yang Xiuzhen; Xu Zheming; Chen Zhongyu; Chen Guangjie; Tang Daxing; Ye Jingjing; Fu Junfen (Journal of Ultrasonography)
The present study aimed to assess the diagnostic efficacy of contrast-enhanced voiding urosonography (ceVUS) using SonoVue for evaluating duplex kidneys, and to compare it with fluoroscopic voiding cystourethrography (VCUG).